Core beliefs as predictors of mental toughness amongst competitive adolescent tennis players - Du Toit, Hanli (University of the Free State, 2014)
Research interest in mental toughness (MT) has increased significantly over the past decade. Numerous theories regarding the nature and development of MT have been proposed, however, no attempt appears to have been made to explore the cognitive behavioural mechanisms that might underpin MT. Consequently, this study aims to investigate whether core beliefs, as defined from within a Rational Emotive Behaviour Therapy (REBT) perspective, are predictive of MT. To this end, a convenience sample of 134 competitive adolescent tennis players aged between 14 and 19 years (M = 15.57; 46.3% female) was recruited and asked to complete measures of MT and core beliefs. Rational beliefs were positively correlated with MT, while irrational beliefs were generally negatively correlated with MT. Moderated hierarchical regression analyses revealed that level of competition moderated the relationship between core beliefs and the control component of MT. The results of the hierarchical regression analyses indicated that while rational beliefs failed to predict a significant proportion of the variance in the sample’s MT, irrational beliefs did emerge as a significant predictor of MT. Irrational beliefs were negatively associated with self-confidence and control. At the level of specific irrational beliefs, demand for achievement and need for approval were predictive of control among the less accomplished players in the sample. These forms of irrational thinking were also negatively associated with control among these participants. Self-downing beliefs predicted determination and positive cognition in the total sample. Self-downing was negatively correlated with these particular components of MT. Other-downing also emerged as a predictor of positive cognition. Moreover, this irrational belief was negatively associated with positive cognition. vi The study suggests that certain core beliefs are predictive of MT amongst competitive adolescent tennis players. Irrational beliefs appear to be a statistically and practically significant predictor of various aspects of MT in this population. These findings suggest that REBT is a suitable perspective from which to conceptualise the cognitive behavioural mechanisms involved in MT. Furthermore, REBT-based interventions may have utility in the development and maintenance of MT among adolescent athletes.

Die belangstelling in mental toughness (MT) navorsing het beduidend tydens die laaste dekade toegeneem. Verskeie teoriee rakende die aard en die ontwikkeling van MT is voorgestel. Geen pogings is egter aangewend om die kognitiewe gedragsmeganismes wat moontlik onderliggend aan MT is, te ondersoek nie. Gevolglik poog die studie om ondersoek in te stel of kernoortuigings, soos gedefinieer vanuit n Rationele Emotiewe Gedragsterapie (REBT) perspektief, voorspellend van MT is. ‘n Gerieflikheidsteekproef van 134 kompeterende adolesente tennisspelers, tussen die ouderdom van 14 en 19 jaar (M = 15.57; 46.3% vroulik), is vir die studie gewerf. Deelnemers het meetinstrumente van beide MT en kernoortuigings voltooi. Rasionele oortuigings is positief met MT gekorreleer, terwyl irrasionele oortuiginge oor die algemeen n negatiewe korrelasie met MT gehad het. Gemodereerde hierargiese regressie analise dui daarop dat vlak van kompetisie die verhouding tussen kern oortuiginge en die MT komponent, beheer, modereer. Hierargiese regressie analise resultate dui daarop dat rasionele oortuiginge nie daarin slaag om n beduidende proporsie van die variansie in die steekproef te voorspel nie, terwyl irrasionele oortuigings wel as beduidende voorspeller van MT bepaal is. Irrasionele oortuiginge is negatief geassosieer met selfvertroue en beheer. Op spesifieke irrationele oortuiging vlak, was behoefte aan prestasie en behoefte aan goedkeuring voorspellend van beheer onder die laer presterende spelers in die steekproef. Hierdie irrasionele denkvorms is ook negatief geassosieer met die steekproef se beheer komponent. Self-afbrekende oortuiginge was vir die totale steekproef voorspellend van determinasie en positiewe kognisie. Self-afbreking was ook negatief gekorreleerd met dieselfde komponente van MT. Ander-afbreking was ook voorspellend van positiewe kognisie. Verder was irrasionele oortuiginge ook negatief geassosieer met positiewe kognisie. Die studie dui daarop dat sekere kernoortuigings voorspellend van MT onder kompeterende adolesente tennisspelers is. Irrasionele oortuigings blyk beide ‘n statisties en pratiese beduidende voorspeller van verskeie aspekte van MT vir die populasie te wees. Hierdie bevindinge stel dus voor dat REBT n toepaslike perspektief is om die kognitiewe gedragsmeganismes betrokke in MT te konseptualiseer. Verder mag REBT-gebasseerde intervensies gebruik hê vir die ontwikkeling en instanthouding van MT onder adolesente atlete.
Dissertation (M.A. (Psychology))--University of the Free State, 2014
Keywords: Tennis; Adolescents; Rational beliefs; Irrational beliefs; Positive cognition; Mental toughness; Determination; REBT; Demand for achievement; Need for approval; Self-downing; Other-downing; Tennis players